Knowledge, attitude and practice of preventing spread of COVID-19 amongst orthopaedic surgeons and residents in a tertiary care hospital in Navi-Mumbai - Samant, Prakash D.; Sane, Rohit M. (International Journal of Research in Orthopaedics, 2020)
Background: With on-going coronavirus pandemic, there is high incidence of COVID-19 occupational risk exposure among health care professionals. The aim of this study was to assess the knowledge, attitude and practice (KAP) amongst orthopaedic surgeons and residents regarding prevention of spread of COVID-19 at a tertiary care hospital. Methods: A cross-sectional, observational, web-based questionnaire study was conducted at orthopaedic department of a tertiary care hospital in Navi Mumbai. The study included orthopaedic surgeons and residents of either sex. A predesigned KAP questionnaire was used to assess the knowledge, attitude and practice regarding prevention of spread of COVID-19. The web-based questionnaire was circulated to eligible participants and the responses obtained were analysed. Results: Overall, the knowledge regarding hand hygiene, mask etiquette and COVID-19 diagnoses was high. Majority participants knew the proper technique of personal protective equipment (PPE), but few 25% and 35% lacked correct technique for donning and doffing of PPE respectively. Majority participants knew the indications and pre/post-operative protocols for orthopaedic surgeries in COVID-19. Around 40% only knew the type of pressure system used in the COVID-19 operation theatre (OT). Majority felt that mask, hand hygiene and PPE were essential kit for prevention. In practice, majority participants were taking drug prophylaxis and were adequately practicing mask/hand hygiene. Conclusions: Overall, KAP regarding prevention of spread of COVID-19 among orthopaedicians were adequate. Further formal preventive education on COVID-19 and structured hands-on experience workshops are necessary to advance the proper techniques of PPE handling.